Educational Services for Disabled Children at SDN Umbul Kapuk, Serang City - Yusup, Maulana; Hafidoh, Hafidoh; Ningtias, Diniya; Sofia Rizqia, Mila; Suhernah, Suhernah; Wijaya, Sastra (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research discusses educational services for children with disabilities at SDN Umbul Kapuk Serang City. In this study, the formulation of the problem is how educational services for children with disabilities at SDN Umbul Kapuk Serang City. The purpose of the research is to understand the educational services for children with disabilities at SDN Umbul Kapuk Serang City. The research method uses a descriptive qualitative method approach. The results of the research in the implementation of the inclusive education program at SDN Umbul Kapuk Kota Serang include public schools, the participation of residents plays a very small or less active role, their role is only limited if they have hyperactive children. Community participation in planning, if residents have suggestions they convey in the meeting forum or through the association. The school in decision-making in the inclusive education program, namely every activity in any form that will be implemented, will be discussed in advance with school residents as a result of decisions from deliberations and meetings. School community participation in evaluating the implementation of inclusive education programs includes school residents always providing input on programs that have been carried out by schools through meetings and also proposing counseling activities about dealing with special students. The school does not yet have a special assistant teacher (GPK) because of the limited training for teachers to teach inclusive classes and so far there has been no good from the government. For class design, it is designed to be as comfortable as possible to facilitate learning such as space areas, subject matter is generally the same as other students, physical training is prioritized, learning evaluation includes making improvements, receiving suggestions such as input from peer teachers or through discussions with expert teachers or teachers who teach in inclusive schools, inhibiting and supporting factors are the low knowledge of school residents about inclusive education.